Miskonsepsi Siswa Dalam Bidang Studi Kimia: - Sabekti, Ardi Widhia (Program Studi Pendidikan Kimia, Fakultas Keguruan dan Ilmu Pendidikan Universitas Maritim Raja Ali Haji, 2015)
Formal thinking, memorize, mathematical operation, visuospatial, and multiple representations (MRs) abilities are required in studying chemistry. Various abilities required in studying chemistry makes chemistry being a difficult subject to study. This difficulty may induce incorrect understanding when occurs consistently may lead to a misconception. The other sources of studentâs misconception are internal factors of students such as daily life experience and external factors such as textbooks, media, language, and school instruction.